ANALISIS DAMPAK PERBEDAAN TIPE KEPRIBADIAN PASANGAN TERHADAP PENYEBAB FENOMENA PERCERAIAN USIA MUDA - Tri Utami Febriyani; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
The phenomenon of young divorce due to differences in the personality types of couples as a determinant of differences in the perspective and life values of couples is a significant factor in the phenomenon of young divorce in our country. It is necessary to analyze the impact of differences in the personality types of couples on the phenomenon of young divorce, and of course it is also important to explain other factors that can affect the relationship of couples. Such as poor communication levels, an imbalance of abilities, or limited skills in conflict control, can all exacerbate the effects of personality type differences. Therefore, it is important for young couples to develop all the potential changes they have to achieve equality and harmony in their relationship through effective communication skills. In this research, a common writing method is used, namely Literature Review. The results of the research discussion of this literature review article contain an Analysis of the Impact of Differences in Spouse Personality Types on the Causes of the Young Age Divorce Phenomenon, namely the existence of a mismatch in the communication style between spouses can cause various misconception problems that can lead to divorce. Suggestions that researchers can give are the need for a more exclusive pre-marital teaching about the types of personality of couples and teaching how to manage the differences that occur between couples.